Keefektifan Group Counseling - Person Centered (GC-PC) untuk Meningkatkan Penyesuaian Diri Santri di Pesantren Walyatalaththof Darussalam - Fa’izah Nurul Hidayati; Akhmad Fajar Prasetya (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The purpose of this study was to measure the effectiveness of group counseling services using the Individual-Oriented approach in supporting students to adapt at the Walyatalaththof Darussalam Kebumen Islamic Boarding School. The type of research applied in this study was a quantitative approach with a pre-experimental design research method through pretest and posttest in one group. This study was a pre-experimental design with a pretest-posttest design in one group to determine the results of the treatment more precisely because it can be compared with the conditions before the treatment was given. The subjects of the study were class VII students of PP Walyatalaththof Darussalam Kebumen, namely 6 students who had low self-adjustment criteria. The study was conducted in 8 sessions, each for 40 minutes. The researcher collected data by utilizing a self-adjustment scale. Based on the results of the research analysis, it was obtained that, (1) Before participating in group counseling with a person-centered approach, the Subjects got an average score of 60.66, which was included in the "low" category. After undergoing a group counseling session with a person-centered approach, the subjects experienced an increase in value from the low category to the high category, with an average value reaching 96. The results of the analysis showed a significance value of 0.000. By considering this value which is below 0.05, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) must be rejected. This shows that group counseling services with a person-centered approach are effective in improving the adjustment abilities of students at the Walyatalaththof Darussalam Kebumen Islamic Boarding School.